2021
DOI: 10.1007/s13204-021-02054-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Synthesis and characterization of CuO nanoparticles and evaluation of their bactericidal and fungicidal activities in cotton fabrics

Abstract: Textiles functionalized with copper oxide nanoparticles (CuO NPs) have become a favourable material to inhibit the spread of diseases due to their anti-microbial properties. In the present work, a successful procedure for in situ growth of CuO NPs in textiles was developed. Results showed that the combination of in situ synthesis and pad–dry–cure method promoting a uniform and dense adsorption of nanoparticles on the surface of the fabrics. The CuO NP-coated fabrics was characterized using XRD, SEM, EDX, TEM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Metal oxides commonly used for antibacterial purposes include the following: Ag 2 O, ZnO, SiO 2 , CuO, MgO, and CaO [9,10]. Several studies have reported that copper oxide is highly sensitive to Gram-positive (B. subtilis CN2, Candida albicans) and Gram-negative (P. aeruginosa CB1, E. coli) microorganisms [11][12][13]. To enhance the performance of copper oxide (CuO)-based antibacterial materials, surface modifications are usually performed with biocompatible surface-coating materials, such as polymers [14], chitosan [15], and polydopamine (PDA) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxides commonly used for antibacterial purposes include the following: Ag 2 O, ZnO, SiO 2 , CuO, MgO, and CaO [9,10]. Several studies have reported that copper oxide is highly sensitive to Gram-positive (B. subtilis CN2, Candida albicans) and Gram-negative (P. aeruginosa CB1, E. coli) microorganisms [11][12][13]. To enhance the performance of copper oxide (CuO)-based antibacterial materials, surface modifications are usually performed with biocompatible surface-coating materials, such as polymers [14], chitosan [15], and polydopamine (PDA) [16].…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticles and structures are almost identical in size to biological molecules, which makes them an interesting candidate for biological study in vivo and in vitro (Nienhaus et al, 2020). They would have a wide range of uses in synthetic textiles; biomedical, surgical, and water treatment; equipment; food processing; and packaging (Alagarasan et al, 2021).…”
Section: Deposition Methods Of Nanoparticles On a Fabric Substratementioning
confidence: 99%
“…The inhibitory zone were detected using amphotericin B as a positive control. Three independent assays were conducted [ 26 ].…”
Section: Methodsmentioning
confidence: 99%